2018
DOI: 10.1021/acsomega.7b01766
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effects of Methyl-β-cyclodextrin on Spiramycin Production and Physical–Chemical Characterization of Nonhost@Guest Complexes

Abstract: Spiramycin is a macrolide antibiotic and antiparasitic that is used to treat toxoplasmosis and various other infections of soft tissues. In the current study, we evaluated the effects of α-cyclodextrin, β-cyclodextrin, or methyl-β-cyclodextrin supplementation to a synthetic culture medium on biomass and spiramycin production by Streptomyces ambofaciens ATCC 23877. We found a high stimulatory effect on spiramycin production when the culture medium was supplemented with 0.5% (w/v) methyl-β-cyclodextrin, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…for H1, H2, and H3, respectively. This result is similar to those reported that β-CD elicits poor inhibition effect on Gram-positive bacteria activity [41][42][43][44]. Thus, this antimicrobial study shows that the optimum hydrogel matrix, H0 is ideal for antimicrobial biomedical application such as wound dressing/treatment while the optimum hydrogel, H1 is suitable for microbial biotechnology application such as metabolic engineering of amino acids.…”
Section: 3supporting
confidence: 90%
See 1 more Smart Citation
“…for H1, H2, and H3, respectively. This result is similar to those reported that β-CD elicits poor inhibition effect on Gram-positive bacteria activity [41][42][43][44]. Thus, this antimicrobial study shows that the optimum hydrogel matrix, H0 is ideal for antimicrobial biomedical application such as wound dressing/treatment while the optimum hydrogel, H1 is suitable for microbial biotechnology application such as metabolic engineering of amino acids.…”
Section: 3supporting
confidence: 90%
“…This structural characteristic makes β-CD excellent for improving loading, swelling, reinforcement and prolonging the release of materials [35,39,40]. Also, β-CD has been reported to have low or almost zero antimicrobial activity [41][42][43] especially against Gram-positive bacteria such as S. ambofaciens ATCC 23877 [43], and S. aureus [44]. To enhance fixation of hydrophobic agents as well as crosslinking, β-CD was selected to be incorporated into the hydrogel matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have used CDs to improve the production efficiency of different compounds. For instance, production efficiency of spiramycin was enhanced by CDs [ 121 ]. Modified β-CDs also increase the rate of deacetylation of spironolactone [ 122 ].…”
Section: Other Applicationsmentioning
confidence: 99%
“…The composition of R2 agar is reported [ 82 ]. For fermentation experiments, S. ambofaciens strains were cultivated in shake flasks at 28 °C on a rotary shaker at 200 rpm as described [ 34 , 83 ].…”
Section: Methodsmentioning
confidence: 99%
“…Spiramycin production by S. ambofaciens broth cultures was assessed by high-performance liquid chromatography-electrospray ionization-mass spectrometry (HPLC-ESI-MS) as described [ 83 ]. At different time intervals, supernatants were filtered through Phenex-RC membrane (0.45 mm; Phenomenex).…”
Section: Methodsmentioning
confidence: 99%